A novel interaction between AD risk genes synaptojanin 1 and reticulon‐3 potentially impacts synaptic function and endo‐lysosomal trafficking during disease development and progression: Molecular and cell biology: Endo‐lysosomal/trafficking dysfunction. (7th December 2020) - Cai, Dongming; Huang, Min; Cao, Jiqing; Hou, Jianwei; Zhu, Li; Zhang, Larry; Pero, Adriana; Guo, Lei; T.C.W., Julia; Zhong, Minghao; Goate, Alison M.; Zhang, Bin; et al.
Abstract: Background: APOE4 is the strongest genetic risk factor for developing sporadic AD with Aβ‐dependent and Aβ‐independent effects on disease pathogenesis. However, molecular signaling mechanisms underlying the detrimental effects of APOE4 on synaptic and cognitive function are not fully elucidated. Methods: We integrated large‐scale human postmortem RNA expression datasets from the AMP‐AD consortium with a total of 1448 human postmortem brain samples representing 5 different brain regions from hundreds of LOAD patients and non‐demented subjects to perform multiscale network analysis. Gene‐regulatory networks for female and male AD were reconstructed and modules with different functional categories and cellular specificity were identified for each network and rank‐ordered based on their relevance to LOAD pathology. The modular differential connectivity and key driver analysis were then performed to identify key drivers with sexually dimorphic expression patterns or differentially respond to APOE genotypes between sexes. Results: In this study, we identified synaptojanin 1 ( synj1 ), a PIP2 ‐degrading enzyme with functional roles implicated in AD pathogenesis by our laboratory and others, as a key driver in AD networks that is associated with key regulators of synaptic function such as reticulon 3 ( RTN3 ). The protein expression of both synj1 and RTN3 is increased in human and mouse brains of APOE4 + carriers. We have also detected the interaction between synj1 and RTN3 in whole brain lysate and synaptosomal fraction through co‐IP that is modified by APOE genotypes and AD status. In addition, we observed enlarged lysosomes in APOE4/4 iPSC‐derived neuron and astrocyte co‐culture when compared to APOE3/3 counterparts. Down‐regulation of synj1 or over‐expression of RTN3 dramatically ameliorated these phenotypes. Conclusions: Based on these findings, we propose a model that the interaction between synj1 and RTN3 under physiological conditions may play important roles in regulation synaptic function and endo‐lysosomal trafficking. In APOE4 + brains, increased synj1 levels may impair intracellular trafficking of RTN3 from tubular ER to vesicular compartments leading to RTN3 retention within ER tubules with reduced distribution to downstream compartments which may contribute to reduced RTN3 degradation, compromised ER integrity, and impaired synaptic function and endo‐lysosomal trafficking.